A methodological approach for purification and characterization of human serum albumin. Issue 6 (1st November 2016) - Raoufinia, Ramin; Mota, Ali; Nozari, Samira; Aghebati Maleki, Leili; Balkani, Sanaz; Abdolalizadeh, Jalal
ABSTRACT: As the most predominant protein in plasma, albumin is synthesized in the liver. Given to various applications of albumin as biopharmaceutical agent, the annual demand for it is 500 tons in the world, which is the highest in the biomedical solutions demand ranking. There exist different procedures for production of albumin. The aim of this study was the purification of human serum albumin (HSA) using immunoaffinity chromatography. After immunization of rabbits, passive immunodiffusion and indirect ELISA tests were applied for assessment of polyclonal antibody production against HSA. Purification was performed by ion exchange chromatography (IEC) and protein G affinity chromatography. The produced anti-HSA IgG was attached to the CNBR-activated Sepharose and applied for albumin purification from human serum. Western blotting (WB) analysis and heat-induced insolubility were performed for functional and stability measurement assessment of immunoaffinity purified HSA, respectively. The optimum titer of anti-HSA determined by indirect ELISA was 256000. The SDS-PAGE showed that the purity rate of albumin was approximately 98% and WB confirmed the HSA functionality. Also, the heat-induced insolubility of immunoaffinity purified HSA was the same as the commercial HSA. Affinity chromatography using produced polyclonal antibody would be a robust method for purification of HSA.